Gaya Hidup Berisiko melalui Aktivitas Revenge Porn dalam Konteks Korban Toxic Relationship di Media Sosial - Mola, Archangela G. D. H.; Nurhadiyanto, Lucky (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The revenge porn is closely related to toxic relationships which is a part of Online Gender-BasedViolence (KBGO) which does not recognize by gender and has been widespread in the last fewyears on social media. Using a qualitative research method and descriptive approach, the authorscollect data by observing and interviewing victims of toxic relationships in the practice of revengeporn on social media. The analysis was carried out from a victimological perspective by using thelifestyle exposure theory to see if the victim's involvement from the role and lifestyle in supportingthem to be indicated being victims. The conclusion of this research is someone can potentiallybecome a victim of revenge porn in toxic practices because they take advantage of the victim'sweaknesses when the two of them are still in a dating relationship through an indication process. Inaddition, someone has the potential to become a victim of revenge porn practices due to anvariables in terms of the victim's lifestyle such as excessive dating style, lack of self-control, wronguse of social media, inability to refuse in toxic relationship conditions, and the existence of familyrelationships that weak.